BCL2 enhances survival of porcine pluripotent stem cells through promoting FGFR2. (26th October 2020) - Zhu, Zhenshuo; Pan, Qin; Zhao, Wenxu; Wu, Xiaolong; Yu, Shuai; Shen, Qiaoyan; Zhang, Juqing; Yue, Wei; Peng, Sha; Li, Na; Zhang, Shiqiang; Lei, Anmin; et al.
Abstract: Objectives: The establishment of porcine pluripotent stem cells (pPSCs) is still a critical topic. However, all pPSCs were failed to contribute to efficient chimeric pig and were extremely sensitive to changes of culture conditions. This study aimed to investigate the role of BCL2 in pPSCs and further explain the mechanism. Materials and Methods: Porcine BCL2 gene was cloned and overexpressed in porcine induce pluripotent stem cells (piPSCs). Digital RNA‐seq was performed to explain the mechanism of anti‐apoptosis. Finally, the cells carrying BCL2 were injected into mouse early embryo to evaluate its chimeric ability. Results: Here, we found that overexpression of porcine BCL2 gene significantly improved the survivability of piPSCs and the efficiency of embryonic chimerism, and did not wreck the pluripotency of piPSCs. Furthermore, the Digital RNA‐seq analysis revealed that BCL2, as a downstream gene of the PI3K signal pathway, enhanced the expression of PI3K signal pathway receptors, such as FGFR2, and further promoted oxidoreductases activity and lipid metabolism, thus maintaining the survival and pluripotency of piPSCs. Conclusion: Our data not only suggested that porcine BCL2 gene could enhance the survivability and chimeric ability of pPSCs, but also explained the positive feedback mechanism in this process, providing strong support for the chimeric experiment of pPSCs. Abstract : Overexpression of porcine BCL2 gene promotes the expression of FGFR2 to resist cell death under conditions of stress. Furthermore, the survival rate and chimerism efficiency of porcine induce pluripotent stem cells were significantly improved.